An Analytical Model for the Combination of AI & IoT in Sustainable Maintenance Systems for Agriculture Machine Tools - Mohanad Jundi Mukheef; Ali Hussein Al-Safaar; Ali Abdulqader Mohammed Ali Al-Zaidi; Yaseen Sabah Kamel; Fahad Raad; Fahad Raad (Eximia, 2025)
This article seeks to underscore the vital importance of integrating artificial intelligence (i.e. Practice has proved that the conventional maintenance mode is not able to meet the needs of modern agricultural mechanization and lead to operation losses and cost increase. In order to address these challenges, this research introduces an integrated analytic model formed by a set of data acquisition with sensors, the network communication technologies at edge and cloud level to converge all the collected information from field devices and artificial intelligence techniques for prediction of failures in equipment domain and make decisions in real time about repairs of devices. It consists of five integrative modules: sensing, communication, intelligent analysis, maintenance management and sustainability layer that to optimize the performance effectiveness and prolong the life cycle of equipments. By reviewing recent literature. The study points out a lack in existing models, which are sometimes not very integrated. It provides a theory view for constructing maintenance system in further actual applications. The model will contribute to fewer sudden breakdowns, cost savings in operations and sustainable smart agriculture.